MCL-1 gains occur with high frequency in lung adenocarcinoma and can be targeted therapeutically - Munkhbaatar, Enkhtsetseg; Dietzen, Michelle; Agrawal, Deepti; Anton, Martina; Jesinghaus, Moritz; Boxberg, Melanie; Pfarr, Nicole; Bidola, Pidassa; Uhrig, Sebastian; Höckendorf, Ulrike; Meinhardt, Anna-Lena; Wahida, Adam; et al. (Nature Communications, 2020)
Evasion of programmed cell death represents a critical form of oncogene addiction in cancer cells. Understanding the molecular mechanisms underpinning cancer cell survival despite the oncogenic stress could provide a molecular basis for potential therapeutic interventions. Here we explore the role of pro-survival genes in cancer cell integrity during clonal evolution in non-small cell lung cancer (NSCLC). We identify gains of MCL-1 at high frequency in multiple independent NSCLC cohorts, occurring both clonally and subclonally. Clonal loss of functional TP53 is significantly associated with subclonal gains of MCL-1. In mice, tumour progression is delayed upon pharmacologic or genetic inhibition of MCL-1. These findings reveal that MCL-1 gains occur with high frequency in lung adenocarcinoma and can be targeted therapeutically.